High NESTIN Expression Marks the Endosteal Capillary Network in Human Bone Marrow - Panvini, Francesca M.; Pacini, Simone; Montali, Marina; Barachini, Serena; Mazzoni, Stefano; Morganti, Riccardo; Ciancia, Eugenio M.; Carnicelli, Vittoria; Petrini, Mario (Frontiers in Cell and Developmental Biology, 2020)
Hematopoiesis is hosted, supported and regulated by a special bone marrow (BM) microenvironment known as “niche”. BM niches have been classified based on micro-anatomic distance from the bone surface into “endosteal” and “central” niches. Whilst different blood vessels have been found in both BM niches in mice, our knowledge of the human BM architecture is much more limited. Here, we have used a combination of markers including NESTIN, CD146 and αSMA labelling different blood vessels in benign human BM. Applying immunohistochemical/immunofluorescence techniques on BM trephines and performing image analysis on almost 300 microphotographs, we detected high NESTIN expression in BM endothelial cells (BMECs) of small arteries (A) and endosteal arterioles (EA), and also in very small vessels we named NESTIN+ capillary-like tubes (NCLTs), not surrounded by sub-endothelial perivascular cells that occasionally reported low levels of NESTIN expression. Statistically, NCLTs were detected within 40 μm from bone trabeculae, frequently found in direct contact to the bone line and spatially correlated with hematopoietic stem/progenitor cells. Our results support the expression of NESTIN in human BMECs of EA and A in accordance with the updated classification of murine BM micro-vessels. NCLTs for their peculiar characteristics and micro-anatomical localization have been here proposed as transitional vessels possibly involved in regulating human hematopoiesis.